Recommendations of PM Task Force on Credit to MSEs: A Critical Analysis - Rautela, Sanjay; Somani, M. D (Journal of Commerce and Trade, 2011)
The MSEs constitute over 90% of total enterprises in most of the economies and are credited with generating the highest rates of employment growth and account for a major share of industrial production and exports. In India also, the MSEs play a pivotal role in the overall industrial economy of the country. They are largest employment provider only after the agricultural sector. The MSE account for 13% of GDP of the nation, and their output constitute about 39 percent share of the value addition in manufacturing sector & about 33% of total export from India. Realizing the potential of this sector our Prime Minister has set up a task force under the chairmanship of principal Secretary to address the issues of MSE Sector. The Task Force covers the issues of Credit, Marketing, Labour, Exit Policy, Infrastructure/Technology/Skill Development, Taxation and Special Package for North East/Jammu & Kashmir. The Task Force submitted its report in the month of January 2010. For any unit to start & function smoothly, money is essential, as such, credit can be termed as lifeline of any unit in-spite of its size, whether small or large. The issue of credit comprises of availability of adequate timely credit, Cost of credit, Collateral requirement, Access to equity capital, Rehabilitation of sick units etc. The suggestions made by us in this paper, if implemented, will definitely make the task of implementing as well as monitoring agency very easy.